Genetic algorithm tuning based PID Controller for liquid-level tank system - Mohammed Obaid, Ali; S. P., Koh; K. H, Chong; S.K., Tiong; Zeyad Assi, Obaid (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.